2018
DOI: 10.1590/1678-4685-gmb-2017-0109
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and expression of the ABC family (G group) in ‘Dangshansuli’ pear (Pyrus bretschneideri Rehd.) and its russet mutant

Abstract: The plant genes encoding ABCGs that have been identified to date play a role in suberin formation in response to abiotic and biotic stress. In the present study, 80 ABCG genes were identified in ‘Dangshansuli’ Chinese white pear and designated as PbABCGs. Based on the structural characteristics and phylogenetic analysis, the PbABCG family genes could be classified into seven main groups: classes A-G. Segmental and dispersed duplications were the primary forces underlying the PbABCG gene family expansion in ‘Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Many candidate genes involved in suberin biosynthesis in both russet pears and apples have been identified via transcriptional analysis, including genes encoding BAHD family acyltransferases, ω‐hydroxypalmitate‐ O ‐feruloyl transferase (HHT), glycerol phosphate acyltransferase (GPAT), 3‐ketoacyl‐CoA synthase (KCS), ATP‐binding cassette (ABC) transporters, MYB93‐like transcription factors, and acyltransferases. Genes involved in lignin biosynthesis such as those encoding caffeic acid 3‐ O ‐methyltransferase (COMT), caffeoyl CoA‐ O ‐methyltransferase (CCOAOMT), cinnamoyl‐CoA reductase (CCR), cinnamyl alcohol dehydrogenase (CAD), and peroxidase (POD) were also found in transcriptome datasets in both russet apple and pear fruits (Hou et al., 2018; Justin et al., 2015; Legay et al., 2015; Wang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many candidate genes involved in suberin biosynthesis in both russet pears and apples have been identified via transcriptional analysis, including genes encoding BAHD family acyltransferases, ω‐hydroxypalmitate‐ O ‐feruloyl transferase (HHT), glycerol phosphate acyltransferase (GPAT), 3‐ketoacyl‐CoA synthase (KCS), ATP‐binding cassette (ABC) transporters, MYB93‐like transcription factors, and acyltransferases. Genes involved in lignin biosynthesis such as those encoding caffeic acid 3‐ O ‐methyltransferase (COMT), caffeoyl CoA‐ O ‐methyltransferase (CCOAOMT), cinnamoyl‐CoA reductase (CCR), cinnamyl alcohol dehydrogenase (CAD), and peroxidase (POD) were also found in transcriptome datasets in both russet apple and pear fruits (Hou et al., 2018; Justin et al., 2015; Legay et al., 2015; Wang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of key enzymes involved in lignin biosynthesis was upregulated to varying degrees during three developmental periods, including 4CL, CAD, and POD ( Supplementary Figure S5 ). In addition, G subfamily proteins of the ABC transporter superfamily were involved in the transport of suberin (Soler et al, 2007 ; Landgraf et al, 2014 ; Hou et al, 2018 ) and were significantly upregulated after ABA treatment, including ABCG5, ABCG11 , and ABCG20 ( Supplementary Figure S6 ). These results indicated that ABA promotes the accumulation of suberin and lignin by regulating the expression of genes at the transcript level.…”
Section: Resultsmentioning
confidence: 99%
“…The increase of oleic acid (C 16:0 ) and palmitic acid (C 18:1 ) in the suberin tissue confirm the biological function of CYP86. Previous studies have shown that PbABCG6 and PbABCG20 may be involved in suberin formation (Hou et al, 2018). PbABCG15 participates in pollen exine development in rice and is also used in the formation of the lipidic cuticle, indicating that it may contribute to an increase in suberin in the exocarp of pears (Wu et al, 2014).…”
Section: Suberin Cutin and Wax Biosynthesismentioning
confidence: 98%
“…In pears and apples, the molecular mechanism of suberin biosynthesis was studied based on transcriptional analysis and masses of candidate genes were identified. The genes encoding COMT (Caffeic acid 3-O-methyltransferase), CCOAOMT (Caffeoyl CoA-O-methyltransferase), CCR (Cinnamoyl-CoA reductase), CAD (Cinnamyl alcohol dehydrogenase), and POD (Peroxidase) in lignin biosynthesis and the genes encoding BAHD family acyltransferase, HHT (ω-hydroxypalmitate-O-feruloyl transferase), GPAT (Glycerol phosphate acyltransferase) faminly, KCS , ATP binding cassette (ABC) transporter, and MYB93-like transcription factor in suberin biosynthesis were considered the key genes for suberized tissue deposition (Wang et al ., 2014a;Lashbrooke et al ., 2015;Legay et al, 2015;Hou et al , 2018). However, much less is known about the specific mechanism by which rainwater affects this complex biosynthesis pathway and a detailed cork synthesis and transmembrane assembly model is needed.…”
Section: Introductionmentioning
confidence: 99%